1992
DOI: 10.1093/infdis/165.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Immunity in Hepatitis C Infection

Abstract: Polymerase chain reaction (PCR) and newer serologic assays for hepatitis C virus (HCV) were used to investigate 19 HCV cross-challenge episodes in chimpanzees. In these cross-challenges, 59% showed seroconversion after challenge, 33% showed reappearance of HCV-associated hepatocellular ultrastructural changes, 5 animals not PCR-positive at the time of challenge showed return of PCR positivity, and 26% developed hepatitis after rechallenge. A total of 74% showed at least one of these signs of reinfection. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(110 citation statements)
references
References 13 publications
4
104
1
1
Order By: Relevance
“…14 Several investigators have also observed that circulating HCV-specific antibodies do not prevent reinfection of chimpanzees with HCV. [15][16][17][18] Therefore, T cells may play a more critical role than antibodies in the resolution of HCV infection.HCV antigen-specific CD8 ϩ T cells have been observed in the peripheral blood and liver of humans and chimpanzees during HCV infection. 5,19 A multispecific cytotoxic T lymphocyte (CTL) response may control HCV replication to some extent, yet the cellular immune response appears to be incapable of clearing the virus in most individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Several investigators have also observed that circulating HCV-specific antibodies do not prevent reinfection of chimpanzees with HCV. [15][16][17][18] Therefore, T cells may play a more critical role than antibodies in the resolution of HCV infection.HCV antigen-specific CD8 ϩ T cells have been observed in the peripheral blood and liver of humans and chimpanzees during HCV infection. 5,19 A multispecific cytotoxic T lymphocyte (CTL) response may control HCV replication to some extent, yet the cellular immune response appears to be incapable of clearing the virus in most individuals.…”
mentioning
confidence: 99%
“…14 Several investigators have also observed that circulating HCV-specific antibodies do not prevent reinfection of chimpanzees with HCV. [15][16][17][18] Therefore, T cells may play a more critical role than antibodies in the resolution of HCV infection.…”
mentioning
confidence: 99%
“…However, various clinical and experimental studies realized in humans and chimpanzees have suggested that frequently protective immunity is not developed following primary infection, a factor that could result in reinfection of patients or animals when exposed to new challenges. [9][10][11] There are two candidate antigens susceptible to induce protective (neutralizing) antibodies: the viral envelope glycoproteins, E1 and E2. Immunization of chimpanzees with recombinant E1 and E2 proteins has been shown to induce protection against a homologous challenge supposedly via the induction of neutralizing antibodies.…”
mentioning
confidence: 99%
“…It was demonstrated in chimpanzees that the presence of persistent infection does not provide protection against subsequent infection with heterologous and even with homologous strains. [56][57][58] As the neutralizing antibodies are isolate-specific, they may be ineffective against other variants present in the complex of quasispecies: in a chimpanzee challenge experiment a hyperimmune anti-HVR1 serum raised against the predominant strain present in the inoculum was able to neutralize the predominant clone but was ineffective against minor variants. 59 However, there is clear evidence for the presence of some crossreactive immunity as convalescent chimpanzees and humans usually do not develop chronic infection upon reexposure.…”
Section: Discussionmentioning
confidence: 99%